Flurbiprofen Axetil Enhances Analgesic Effects of Sufentanil and Attenuates Postoperative Emergence Agitation and Systemic Proinflammation in Patients Undergoing Tangential Excision Surgery - Wujun Geng; Wandong Hong; Junlu Wang; Qinxue Dai; Yunchang Mo; Kejian Shi; Jiehao Sun; Jinling Qin; Mei Li; Hongli Tang (Hindawi Limited, 2015)
Objective. Our present study tested whether flurbiprofen axetil could reduce perioperative sufentanil consumption and provide postoperative analgesia with decrease in emergency agitation and systemic proinflammatory cytokines release. Methods. Ninety patients undergoing tangential excision surgery were randomly assigned to three groups: (1) preoperative dose of 100 mg flurbiprofen axetil and a postoperative dose of 2 μg/kg sufentanil and 10 mL placebo by patient-controlled analgesia (PCA) pump, (2) preoperative dose of 100 mg flurbiprofen axetil and a postoperative dose of 2 μg/kg sufentanil and 100 mg flurbiprofen axetil by PCA pump, and (3) 10 mL placebo and a postoperative dose of 2 μg/kg sufentanil and 10 mL placebo by PCA pump. Results. Preoperative administration of flurbiprofen axetil decreased postoperative tramadol consumption and the visual analog scale at 4, 6, 12, and 24 h after surgery, which were further decreased by postoperative administration of flurbiprofen axetil. Furthermore, flurbiprofen axetil attenuated emergency agitation score and Ramsay score at 0, 5, and 10 min after extubation and reduced the TNF-α and interleukin- (IL-) 6 levels at 24 and 48 h after the operation. Conclusion. Flurbiprofen axetil enhances analgesic effects of sufentanil and attenuates emergence agitation and systemic proinflammation in patients undergoing tangential excision surgery.